Accounting of liability of the enterprise under national and international accounting standards. (Economics and region, 2019)
The article deals with the order of formation of information and reflection of operations on accounting of obligations of the enterprise in accordance with the norms of national and international accounting standards. The comparative analysis of normative documents in the context of the interpretation of the essence, recognition and classification of obligations of the enterprise is carried out. The common and distinctive features of the method of accounting for the given object are established.
Keywords: obligations; ensuring; national accounting standards; international accounting standards; recognition; classification of obligations